A Learning-Based Steganalytic Method against LSB Matching Steganography - Xia, Zhihua; Yang, Lincong; Sun, Xingming; Liang, Wei; Sun, Decai; Ruan, Zhiqiang (Společnost pro radioelektronické inženýrství, 2011)
This paper considers the detection of spatial domain least significant bit (LSB) matching steganography in gray images. Natural images hold some inherent properties, such as histogram, dependence between neighboring pixels, and dependence among pixels that are not adjacent to each other. These properties are likely to be disturbed by LSB matching. Firstly, histogram will become smoother after LSB matching. Secondly, the two kinds of dependence will be weakened by the message embedding. Accordingly, three features, which are respectively based on image histogram, neighborhood degree histogram and run-length histogram, are extracted at first. Then, support vector machine is utilized to learn and discriminate the difference of features between cover and stego images. Experimental results prove that the proposed method possesses reliable detection ability and outperforms the two previous state-of-the-art methods. Further more, the conclusions are drawn by analyzing the individual performance of three features and their fused feature.
Keywords: Communication security; steganalysis; histogram gradient energy; neighborhood degree histogram; run-length histogram; support vector machine